Chromatography-mass spectroscopy of larvae of large wax moths - Yu. I. Kornievsky; О. I. Panasenko; V. G. Kornievskaya; N. Yu. Boguslavskaya (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Tincture of larvae of large wax moth, as a folk remedy, is known since the middle of the 17th century and was used to treat tuberculosis, chronic bronchopulmonary diseases (including pediatrics), when conventional treatment (antibiotics or other chemotherapeutic methods) does not give a positive result, in obstetrics and gynecology in the treatment of climacteric disorders, infertility, miscarriage and many other diseases, as well as means of delaying aging.